A Cartografia dos Poderes. Da Matriz Africana à Organização Colonial do Espaço - Santos, Maria Emília Madeira (Africana Studia, 2020)
Elaborated in the sequence of the first approaches of colonial powers in Africa, small and medium scale cartography allows the social sciences to have access to data covering wider chronological periods. The maps and charts, made immediately before full military occupation, give us different information on territories and traditional African populations, as well as on the stages of the building of a new colonial order. In this article we show, through the examples of Bié, Chibia and Cuanhama region, the importance of cartography as an historical source fully inter-disciplinary.